(untitled) (Economics and region, 2025)
This article explores the economic importance of quality management within Azerbaijan’s construction sector, alongside the current methodologies employed in the sector. Achieving success in modern construction projects goes beyond mere technical execution; it fundamentally depends on efficient resource utilization, reduction of material wastage, and ensuring projects are completed on schedule and within budget. Meeting these goals requires the implementation of systematic and well-structured quality management practices. The study analyzes investment patterns in the construction sector over a specific timeframe, revealing a 50-75% growth in investments since 2000, which has enabled the adoption of advanced technologies and globally recognized quality management frameworks. The results highlight the vital role these systems play in strengthening the financial resilience of construction companies, optimizing resource allocation, mitigating risks, enhancing customer satisfaction, and facilitating the successful delivery of future projects. The example of PMD Projects LLC, a subsidiary of the prominent Azerbaijani construction company PMD Group LLC, demonstrates that adherence to international standards like ISO 9001:2015 significantly contributes to operational excellence and helps cultivate a positive investment environment. This strategy encompasses not only technical quality but also emphasizes social responsibility and environmental sustainability. Ultimately, the article contends that embedding quality-driven management practices in the construction sector should be considered a strategic element in Azerbaijan’s economic growth strategy, calling for ongoing adoption of comprehensive and institutionalized quality frameworks.